2002
DOI: 10.1291/hypres.25.25
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ2 Pro12Ala Polymorphism and Insulin Resistance in Japanese Hypertensive Patients

Abstract: We investigated the relationship between peroxisome proliferator-activated receptor (PPAR ) Pro12Alasubstitution and insulin resistance in subjects with normal insulin secretory capacity, since it has been reported that PPAR may affect not only insulin resistance but also insulin secretion. We examined 81 Japanese male patients with untreated essential hypertension using the glucose clamp technique. We found 77 subjects with Pro/Pro and 4 subjects with Pro/Ala genotype, and the glucose disposal rate was not si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
(9 reference statements)
2
11
0
2
Order By: Relevance
“…26,31,32 Similar results were observed in other studies performed in other Asian populations, with rare frequency of the Ala12Ala genotype. 33,34 In the present study the allele frequency of alanine was 0.043, similar to the previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…26,31,32 Similar results were observed in other studies performed in other Asian populations, with rare frequency of the Ala12Ala genotype. 33,34 In the present study the allele frequency of alanine was 0.043, similar to the previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…11 The following pair of primers was used for DNA amplification by PCR: 5 0 -CAAGCCCAGTCCTTTCTGTG-3 0 as a sense primer (PPAR-f) and 5 0 -AGTGAAGGAATC GCTTTCCG-3 0 as an antisense primer (PPAR-r) (GenBank accession AB005520). These primers yielded PCR product of 236 bp in length.…”
Section: Genotypingmentioning
confidence: 99%
“…12,13,23 However, only a few studies have successfully shown that a mutation is associated with phenotypes that are related to insulin resistance and associated with hypertension. [24][25][26][27] This study indicates that the CA16 microsatellite polymorphism in the TNFR2 gene is a potential marker for severe hypertension associated with insulin resistance.…”
Section: Discussionmentioning
confidence: 69%